FACIAL VASCULAR LESIONS IN PATIENTS WITH PTERYGOPALATINE GANGLIONITIS - Kolisnyk І.А.; Korotych, N.N.; Pankevych А.I.; Gogol, A.M.; Dobroskok, V.A. (World of Medicine and Biology, 2017)
The paper presents the findings of the study of facial vascular lesions in patients with pterygopalatine ganglionitis (PPG) depending of the degree of its severity. It has been proved that no facial thermoactivity occurs in the minor PPG; thermoasymmetry has been revealed in 85,7% of patients with the moderate pterygopalatine ganglionitis due to increase of thermoactivity of the face on the average of 0,5°С. The marked thermoasymmetry of the face (0,8°С) has been noted in all patients with the severe pterygopalatine ganglionitis. Notably, if in the moderate PPG we observed the rise of temperature on the affected side. Facial vascularization has been also found. They were insignificant in the minor pterygopalatine ganglionitis. The decrease of the vascular tone and increased blood supply to the vessels of the face has been revealed in the moderate pterygopalatine ganglionitis. On the contrary, in the severe pterygopalatine ganglionitis the increased tone and decreased blood filling of the facial vessels has been detected on the affected side. Such vascular lesions are accompanied by the corresponding clinical picture of the ganglionitis and vegetative manifestations.